1996
DOI: 10.1021/bk-1996-0638.ch024
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Cooperation via Spillover of Oxygen: Dehydration—Dehydrogenation of 2-Butanol over SnO2—MoO3 Catalysts

Abstract: Strong synergetic phenomena in the dehydration-dehydrogenation of sec-butyl alcohol were observed at very low temperature using mechanical mixtures of separately prepared SnO 2 and MoO 3 . The principal effects were an increase in conversion as well as increases in yields and selectivities for butene and methyl-ethyl ketone. Characterization of the solids before and after catalytic tests by X-ray Photoelectron Spectroscopy coupled with Transmission Electron Microscopy, Raman Spectroscopy and X-ray Diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Moreover, the sensitivity to a specific gas of SnO 2 -based sensors can be tuned by doping with different cations (see for example refs −5). It was shown that SnO 2 doped by Mo is sensitive to alcohol detection; it leaves almost unchanged the response to NO 2 , and it has a low response to CO . However, it is also reported that when mixed Mo−Sn oxides are formed, the response to CO increases .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the sensitivity to a specific gas of SnO 2 -based sensors can be tuned by doping with different cations (see for example refs −5). It was shown that SnO 2 doped by Mo is sensitive to alcohol detection; it leaves almost unchanged the response to NO 2 , and it has a low response to CO . However, it is also reported that when mixed Mo−Sn oxides are formed, the response to CO increases .…”
Section: Introductionmentioning
confidence: 99%